SCOPING REVIEW: ANALISIS KONTAMINASI RESIDU PESTISIDA TANAMAN HORTIKULTURA DI INDONESIA DAN DAMPAKNYA TERHADAP KESEHATAN - Sabil, M Arum; Azizah, R.; Ramadhan, Syahrul (Dian Nuswantoro Semarang, 2024)
The agricultural have challenges, namely pests that can inhibit or affect crop yields. Excessive use of pesticides produces residues that can pollute the environment and have an impact on health. This is literature study with a scoping review method. Article searches are conducted through the Google Scholar database. The inclusion criteria in this study are original articles, open access articles, publication articles in the 2013-2023 period, and discussing pesticide residues in horticultural crops. The exclusion criteria are review articles, purschasing articles, publications under 2013. Based on the findings, there are 10 articles are included. The fruit or vegetable studied consisted of 2 studies on chili, 1 of tomato, onion, lettuce, cabbage, orange, cabbage, melon, and kale respectively. The method of examining pesticide residues in all articles uses the Gas Chromatography method. The active substances of pesticides examined consisted of 5 studies on profenofos, 4 studies of chlorpyripos, and 1 study of dimethoate. Total of 5 studies identified pesticide residues on plants. The conclusion from the articles studied fruits and vegetables there are still pesticide residues. It is necessary to have methods of reduction and prevention efforts to reduce the impact of pesticide residues on health and the environment.